Agricultural Development Model and Transformation in Gaum Village, Tasikmadu Subdistrict, Karanganyar Regency - Sinurat, Epram Natanael; Akbar, Exit Sonia; Savitri, Nurul; Fachrozi, Raziz; Anggara, Rifky Kusuma; Antriyandarti, Ernoiz (Research and Social Study Institute, 2024)
This community services activity aims to determine the potential and problems, structural transformation, institutional transformation, technology application, and suitable model regarding the agricultural development in Gaum Village, Tasikmadu Subdistrict, Karanganyar Regency. The methods used were face-to-face interviews with relevant resource persons, observation, and descriptive analysis for data processing. The results reveal that the potential in this village is its vast agricultural land, while the problems faced are crop pests and limited fertilizer with high prices. Structural transformation in the agriculture sector in this village is characterized by a shift from traditional practices with low productivity and even losses to modern practices with higher productivity, even though the commodity prices often fluctuate every year. Institutional transformation in this village tends not to undergo bureaucratic change despite the change of village head. The application of agricultural technology in this village is also not optimal, as the majority of farmers here still apply traditional methods to cultivate their agricultural land. The diffusion model is considered more appropriate to be applied for the agricultural development in Gaum Village. In this context, this model aims to increase agricultural productivity through dissemination of new technologies and knowledges.